Neural Degeneration in the Retina of the Streptozotocin-Induced Type 1 Diabetes Model - Ozawa, Yoko (Hindawi Publishing Corporation, 2011)
Diabetic retinopathy, a vision-threatening disease, has been regarded as a vascular disorder. However, impaired oscillatory potentials (OPs) in the electroretinogram (ERG) and visual dysfunction are recorded before severe vascular lesions appear. Here, we review the molecular mechanisms underlying the retinal neural degeneration observed in the streptozotocin-(STZ-) induced type 1 diabetes model. The renin-angiotensin system (RAS) and reactive oxygen species (ROS) both cause OP impairment and reduced levels of synaptophysin, a synaptic vesicle protein for neurotransmitter release, most likely through excessive protein degradation by the ubiquitin-proteasome system. ROS also decrease brain-derived neurotrophic factor (BDNF) and inner retinal neuronal cells. The influence of both RAS and ROS on synaptophysin suggests that RAS-ROS crosstalk occurs in the diabetic retina. Therefore, suppressors of RAS or ROS, such as angiotensin II type 1 receptor blockers or the antioxidant lutein, respectively, are potential candidates for neuroprotective and preventive therapies to improve the visual prognosis.